2012
DOI: 10.5539/ijel.v2n5p142
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Optimum Length of a Cloze Test?

Abstract: Following Nation' (2009) proposal of 40-50 empty spaces as an optimum length of a cloze test, this study examined whether this length would work according to proficiency level. Three cloze tests, adjusted for each proficiency level, were developed by the researcher for the use at beginning, intermediate and advanced levels. The cloze tests measured participants' reading comprehension and included 40, 45 and 50 empty spaces for the beginning, intermediate and advanced levels respectively. Problematic items of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…Uma das possibilidades adotadas para avaliar a compreensão de leitura é a técnica de Cloze, que tem sido objeto de atenção de estudiosos desde sua proposição por Taylor (1953) até os anos recentes, em que estudos mostram sua adequação como medida rápida e confiável da compreensão de leitura (Bellon-Harn, Credeur-Pampolina, & LeBoeuf, 2013;Briere, Clausing, Senko, & Purcell, 1978;Gellert & Elbro, 2012;Kroeger, Burton, & Preston 2009;Shahnazari-Dorcheh, Roshan, & Hesabi, 2012). No Brasil, o Cloze tem sido bastante usado para o diagnóstico do nível de compreensão de leitura em universitários, visto que consiste na eliminação de alguns vocábulos do texto, que são substituídos por traços.…”
unclassified
“…Uma das possibilidades adotadas para avaliar a compreensão de leitura é a técnica de Cloze, que tem sido objeto de atenção de estudiosos desde sua proposição por Taylor (1953) até os anos recentes, em que estudos mostram sua adequação como medida rápida e confiável da compreensão de leitura (Bellon-Harn, Credeur-Pampolina, & LeBoeuf, 2013;Briere, Clausing, Senko, & Purcell, 1978;Gellert & Elbro, 2012;Kroeger, Burton, & Preston 2009;Shahnazari-Dorcheh, Roshan, & Hesabi, 2012). No Brasil, o Cloze tem sido bastante usado para o diagnóstico do nível de compreensão de leitura em universitários, visto que consiste na eliminação de alguns vocábulos do texto, que são substituídos por traços.…”
unclassified
“…En síntesis, el análisis efectuado parece apoyar el postulado de varios autores (Abraham & Chapelle, 1992;Brown, 2013;Gellert & Elbro, 2013;Shahnazari-Dorcheh et al, 2012;Trace, 2020, entre otros) sobre la validez del cloze (en dependencia de su método de construcción y calificación) para evaluar comprensión global, dado que la puntuación que obtiene el lector puede ser entendida como un indicador de su competencia para emplear las claves textuales. En este sentido, en la presente investigación la dificultad de los blancos referidos a lenguaje especializado varía de modo consistente según la brecha entre los ítems (Trace, 2020) -cantidad de contexto requerido para completarlos-, la que exige que se establezca la conexión entre proposiciones separadas en el texto (Abraham & Chapelle, 1992;Gellert & Elbro, 2013).…”
Section: Discussionunclassified
“…ej., Gellert & Elbro, 2013), los patrones de eliminación de términos (Kleijn, Pander-Maat, & Sanders, 2019), los métodos de calificación (Kleijn et al, 2019;O'Toole & King, 2010) y, en menor medida, la dificultad de los ítems (Trace, 2020;Trace, Brown, Janssen, & Kozhevnikova, 2017). La primera pregunta conforma un área de ininterrumpido debate, que enfrenta a quienes consideran que solo evalúa comprensión local (por ejemplo, Carlisle & Rice, 2004, en Trace et al, 2017 con aquellos que sostienen que puede ponderar la coherencia global, constituyéndose así en una medida válida y rápida de la competencia lectora (Gellert & Elbro, 2013;Kleijn et al, 2019;Shahnazari-Dorcheh, Roshan, & Hesabi, 2012;Trace, 2020).…”
Section: Introductionunclassified
“…Lower scores indicate more difficulty in understanding the text. The rationale behind this test is that the respondent must be susceptible to semantic and syntactic restrictions in each context to fill in the blanks(Shahnazari-Dorcheh, Roshan, & Hesabi, 2012). The length of the cloze test studied byShahnazari-Dorcheh et al (2012) found that the length of the cloze test depends on the proficiency level.…”
mentioning
confidence: 99%
“…The rationale behind this test is that the respondent must be susceptible to semantic and syntactic restrictions in each context to fill in the blanks(Shahnazari-Dorcheh, Roshan, & Hesabi, 2012). The length of the cloze test studied byShahnazari-Dorcheh et al (2012) found that the length of the cloze test depends on the proficiency level. The authors concluded that at the advanced proficiency level, a long test including 50 empty spaces is reliable and a short test including 20 to 25 spaces is more reliable at beginner and intermediate proficiency levels.…”
mentioning
confidence: 99%